2013
DOI: 10.1002/chem.201204315
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Controlled Reversible Formation of a Supramolecular Hyperbranched Polymer Showing Fluorescence Switching

Abstract: A π-conjugated AB2 monomer 1 with a dibenzo[24]crown-8 (DB24C8) ring and two secondary amine centres has been synthesised. Treatment of a solution of 1 in dichloromethane with trifluoroacetic acid (TFA) leads to protonation of the amine groups, and then the DB24C8 rings are threaded by the dialkylammonium ion centres of other monomer molecules, leading to the formation of a supramolecular hyperbranched polymer, TFA-1. Rather strong π-π stacking interactions between the conjugated cores are evident in this poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…The morphology of two supramolecular aggregates was then observed by transmission electron microscopy (TEM), and spherical aggregates were observed for both the AB 2 system and the AB 2 +CD 2 system (Figure b). This morphology was similar to the results previously reported for AB 2 ‐type supramolecular polymers . Furthermore, the average size of spherical aggregates for the AB 2 +CD 2 system (200–600 nm) is larger than for the AB 2 system (180–500 nm).…”
Section: Resultssupporting
confidence: 90%
“…The morphology of two supramolecular aggregates was then observed by transmission electron microscopy (TEM), and spherical aggregates were observed for both the AB 2 system and the AB 2 +CD 2 system (Figure b). This morphology was similar to the results previously reported for AB 2 ‐type supramolecular polymers . Furthermore, the average size of spherical aggregates for the AB 2 +CD 2 system (200–600 nm) is larger than for the AB 2 system (180–500 nm).…”
Section: Resultssupporting
confidence: 90%
“…Taking advantage of the easy modification of macrocyclic host molecules, e.g., crown ether and pillararene, AB 2 -type monomers which simultaneously contain host and guest moieties are most commonly used to construct supramolecular hyperbranched polymers. Gibbson et al reported the construction of supramolecular hyperbranched polymers from self-assembly of an AB 2 monomer containing complementary recognition sites, a bis­( m -phenylene)-32-crown-10 and two paraquat moieties .…”
Section: Supramolecular Polymers With Branch-like and Hyperbranch-lik...mentioning
confidence: 99%
“…On account of the relatively low binding constant of this host–guest system, a high monomer concentration (>100 mM) was required for a high degree of supramolecular polymerization. Supramolecular hyperbranched polymers fabricated through the recognition between dibenzo[24]­crown-8 (DB24C8) moieties and diakylammonium ion centers showed a pH response. , A polymer structure formed under acidic condition, while it degraded in basic solution. Upon successive addition of acid and base to the polymer solution, reversible changes in the fluorescence intensity could be observed over at least 10 cycles .…”
Section: Supramolecular Polymers With Branch-like and Hyperbranch-lik...mentioning
confidence: 99%
“…However, imaging probes and therapeutic agents are usually of high hydrophobicity. Luckily, various building blocks, such as CD, cucurbit[n]uril and sulfonate calixarene can recognize and include certain hydrophobic guest species [36,49], which provide feasibility to obtain supramolecular system with good aqueous solubility [50][51][52][53]. Normally, good aqueous compatibility is basic for biocompatibility.…”
Section: Aqueous Compatibility and Biodegradabilitymentioning
confidence: 99%
“…During biological use, especially in diagnosis and therapy, fast and smart stimuli-responsiveness is highly favored, because the environmental factors in living system could be altered in very limited scope. SDPs, which can respond to internal stimuli such as pH [50,51], redox [14], voltage [50] and enzyme [53], are usually exhibiting good release behavior or high contrast signals when using as delivery vehicles for drugs or imaging probes. At the same time, the ones responsive to external stimuli such as temperature [30,31,56], light [12, 35,55], ultrasonic signal and magnetic field, can be fabricated into smart in vitro diagnosis or therapeutic devices [60][61][62][63][64][65][66][67][68].…”
Section: Stimuli-responsivenessmentioning
confidence: 99%